2014
DOI: 10.1142/s1793545814500096
|View full text |Cite
|
Sign up to set email alerts
|

Influence of absorption in linear polarization imaging of melanoma tissues

Abstract: The contrast mechanism of di®erent polarization imaging techniques for melanoma in mouse skin is studied using both experiments and Monte Carlo simulations. Total intensity, linear polarization di®erence imaging (DPI), degree of polarization imaging (DOPI) and rotating linear polarization imaging (RLPI) are applied and the relative contrasts of these polarization imaging methods between the normal and cancerous tissues are compared. A two-layer absorption-scattering model is proposed to explain the contrast me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The retardance contrast between healthy and obstructed regions of the bladder would be potentially useful to guide augmentation surgeries and monitoring the tissue functionality following tissue engineering therapies . Mueller polarimetry or polarimetric imaging has furthermore been used to investigate muscles , normal and precancerous human cervix , oral and lung tissues , radiofrequency ablated porcine myocardial tissue , skeletal muscle , growth of bacteria colonies , skin including melanoma , animal tissues , bladders , the orientation of collagen fibres in 3‐D space , red blood cell suspensions , etc.…”
Section: The Biomedical Applications Of Mueller‐polarimetric Imagingmentioning
confidence: 99%
“…The retardance contrast between healthy and obstructed regions of the bladder would be potentially useful to guide augmentation surgeries and monitoring the tissue functionality following tissue engineering therapies . Mueller polarimetry or polarimetric imaging has furthermore been used to investigate muscles , normal and precancerous human cervix , oral and lung tissues , radiofrequency ablated porcine myocardial tissue , skeletal muscle , growth of bacteria colonies , skin including melanoma , animal tissues , bladders , the orientation of collagen fibres in 3‐D space , red blood cell suspensions , etc.…”
Section: The Biomedical Applications Of Mueller‐polarimetric Imagingmentioning
confidence: 99%
“…During calculations, we should first determine this angle according to the spatial orientation of the cylinder and the propagation direction of the photon, and then follow the theory of polarized photon scattering at an infinitely long cylinder, which has been demonstrated in detail in Ref. 13. The scattering coefficient of a microsphere is a constant once its size and refractive index are set.…”
Section: Monte Carlo Simulation and Scbmmentioning
confidence: 99%
“…For the absorption effect in ambient media, Li et al proposed a skin model containing a top isotropic layer, a bottom anisotropic layer, and an absorbing medium to explain the contrast mechanism of polarization imaging for melanoma. 13 Dmitry et al proposed an approximate expression to describe the dependence of the degree of residual linear polarization on the absorption of scattering media. 14 Swami et al studied how the absorption of the scattering medium containing spherical scatterers and absorbing medium affects the depolarization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The experimental results on human colon, cervix, and skin cancerous tissues indicated that the backscattering Mueller matrix may serve as a noninvasive tool for cancer diagnosis. [11][12][13] Many tissues contain aligned anisotropic fibrous microstructures, such as the collagen and elastin fibers in epithelial tissues, muscle fibers in cardiac and skeletal muscle tissues. Changes of these fibrous structures can also be characterized by polarization sensitive measurements.…”
Section: Introductionmentioning
confidence: 99%